Concomitant valve surgery is associated with worse outcomes in surgical treatments of post-infarction ventricular aneurysm - Liu, Yuqi; Cai, Ziwen; Xu, Li; Zheng, Yidan; Chen, Ming; Dong, Nianguo; Chen, Si (Frontiers in Cardiovascular Medicine, 2023)
1) Objective: To evaluate the impact of concomitant valve surgery on the prognosis of patients who experienced coronary artery bypass graft (CABG) with/without ventricular reconstruction for the ventricular aneurysm.(2) Methods: In our department, 354 patients underwent CABG with/without ventricular reconstruction for a ventricular aneurysm from July 23rd, 2000 to December 23rd, 2022. A total of 77 patients received concomitant valve surgery, 37 of whom underwent replacement, and 40 of whom underwent repair. The baseline characteristics, prognostic, and follow-up information were statically analyzed.Univariate and multivariate Cox regression analyses were applied to identify the risk factors of long-term outcomes.(3) Results: Compared with patients who did not undergo valvular surgery, patients who experienced concomitant valve surgical treatments had a significantly lower survival rate (p = 0.00022) and a longer total mechanical ventilation time. Subgroup analysis indicated that the options of repair or replacement exhibited no statistically significant difference in postoperative mortality (p = 0.44) and prognosis. The multivariate Cox regression analysis suggested that the pre-operative cholesterol level (HR = 1.68), postoperative IABP (HR = 6.29), NYHA level (HR = 2.84), and pre-operative triglyceride level (HR = 1.09) were independent and significant predictors for overall all-cause mortality after surgery.(4) Conclusion: Concomitant valve surgery was considerably related to a higher risk of postoperative mortality in patients with post-infarction ventricle aneurysms who underwent surgical treatments. No significant difference in the prognosis outcomes was observed between the operating methods of repair or replacement valve surgery.